1999
DOI: 10.1002/(sici)1520-6777(1999)18:5<427::aid-nau3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bladder training, pelvic floor muscle training, or combination training on urodynamic parameters in women with urinary incontinence

Abstract: The purpose of this study was to compare the effect of three conservative interventions: pelvic floor muscle training, bladder training, or both, on urodynamic parameters in women with urinary incontinence. Two hundred four women with genuine stress incontinence (GSI) or detrusor instability with or without GSI (DI ± GSI) participated in a two‐site trial comparing pelvic floor muscle training, bladder training, or both. Patients were stratified based on severity of urinary incontinence, urodynamic diagnosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 16 publications
2
44
1
Order By: Relevance
“…This physiologic mechanism was the rational one for treating patients with overactive detrusor by pelvic¯oor exercises. Several studies have shown that patients with detrusor overactivity may bene®t from behavioral modi®cation and pelvic¯oor rehabilitation techniques [Fantl et al, 1991;Elser et al, 1999]. Although the speci®c mechanisms by which the clinical improvement is achieved are still unknown, it is likely that this is at least partly due to the induced inhibition of detrusor activity by sphincteric contractions, as well as adaptive behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…This physiologic mechanism was the rational one for treating patients with overactive detrusor by pelvic¯oor exercises. Several studies have shown that patients with detrusor overactivity may bene®t from behavioral modi®cation and pelvic¯oor rehabilitation techniques [Fantl et al, 1991;Elser et al, 1999]. Although the speci®c mechanisms by which the clinical improvement is achieved are still unknown, it is likely that this is at least partly due to the induced inhibition of detrusor activity by sphincteric contractions, as well as adaptive behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one studies investigating augmented MUCP were found (Table 1) [14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. One study was excluded because the results combined values for men and women [37].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Eight studies were identified: two studies were unpublished and therefore no data extraction was undertaken. 108,109 Of the remaining six studies, three were completed in the USA, 80,83,94 one in Canada, 93 one in New Zealand 79 and one in the UK. 92 …”
Section: Description Of Studies Of Acceptability and Feasibilitymentioning
confidence: 99%
“…Four studies used a pad test to evaluate severity of urine loss 31,71,73,76,109 (Wyman et al 31 reported in Elser et al…”
Section: Grams Of Urine Lost In 24 Hours (Post Treatment)mentioning
confidence: 99%
See 1 more Smart Citation